PENINGKATAN HASIL BELAJAR PENCERMINAN BANGUN DATAR MENGGUNAKAN MEDIA PAPAN BERPAKU DI SDN 06 SUKARAMAI - Suryani, Suryani; Tampubolon, Budiman; Kresna, Hery (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe general problem of this research is whether by using the media of rigid board on the learning of flat wake reflection can improve student learning result of fourth grade SDN 06 Sukaramai Kapuas Hulu. The method used is descriptive method with class action research form. The research procedure consists of planning, implementation, observation and reflection. The subjects of the fourth grade students who numbered 14 people. Technique of data collecting technique of direct observation and measurement technique. Data collection tool of observation sheet and test of student learning result. The ability of teachers in planning the learning in cycle I obtained an average of 3.68, in cycle II obtained an average of 3.88 and in cycle III obtained an average of 3.93. The ability of teachers to implement flat wake reflection learning using a fixed board media in cycle I obtained an average of 3.03, in cycle II obtained an average of 3.54 and in cycle III obtained an average of 3.93. The average achievement of student learning outcomes in cycle I is 70,71 in cycle II 80 and in cycle III is 87,5. It was concluded that the use of rigid board media on flat wake reflection learning can improve the learning outcomes of fourth graders of SD Negeri 06 Sukaramai Kapuas Hulu. Keywords: Rigid Board Media, Learning Outcomes, Reflection Learning